Determinants of transmission hotspots and filarial infection in households after eight rounds of mass drug administration in India. Issue 11 (10th September 2018) - Srividya, A.; Subramanian, S.; Sadanandane, C.; Vasuki, V.; Jambulingam, P.
Abstract: Objectives: Lymphatic filariasis (LF) elimination through mass drug administration (MDA) of DEC and albendazole have resulted in very low levels of infection in most endemic districts in India. But small pockets with residual microfilaraemia in the community and antigeneamia in children ('hotspots') are a cause of concern. We aimed to identify the determinants of such transmission hotspots and filarial infection in households using data from 33 communities. Methods: The filariasis vector Culex quinquefasciatus was collected from 627 randomly selected households using gravid traps. Parallel data on environmental, entomological, demographical, socio‐economical and behavioural factors were analysed to identify the determinants of hotspots and household‐level infection. Results: Hotspots and non‐hotspots did not differ significantly in terms of socio‐economical and behavioural aspects, but did differ in terms of demographical and environmental factors. Logistic regression revealed that tiled and concrete houses increased the risk of an area being a hotspot by 2.0 and 2.9 times respectively. Presence of Culex breeding habitats was significantly associated with elevated risk of being a hotspot. Proximity of U‐drains to a house increased the risk of filarial infection 5.8 times. Conclusions: An environment suitable to Culex breeding influences continued transmission despite eight rounds of MDA, particularly in hotspots. Proximity to U‐drains increases the risk of infection in households. Implementing localised vector control measures may help interrupt low‐level transmission, thereby reducing the risk of resurgence in the absence of MDA.